P04.01 Synergistic antitumor effects of a combined therapy consisting of immune checkpoint inhibitors and tumor-targeting nanoparticles in glioblastoma - Shevtsov, M (Neuro Oncol, 2018)
BACKGROUND: Immune checkpoint inhibitors are reshaping therapeutic strategies in neuro-oncology. We hypothesize that the anti-cancer activity of immune checkpoint inhibitors could be further enhanced by tumor-targeting theranostic nanoparticles. The 70-kDa heat shock protein (Hsp70) is known to be overexpressed on the membrane of tumor cells, but not on normal cells. Granzyme B specifically targets Hsp70 membrane-positive tumor cells and thereby causes apoptotic cell death. MATERIAL AND METHODS: Superparamagnetic iron oxide nanoparticles conjugated with granzyme B (GrB-SPIONs) were characterized using dynamic light scattering, zeta potential analyzer, magnetometry, nonlinear magnetic response measurements (NLR-M(2)), and transmission electron microscopy techniques. The cytotoxicity of SPIONs was assessed using MTT assay and flow cytometry (annexin V, caspase-3). Targeting of tumor cells was analyzed using confocal and electron microscopy and flow cytometry. Retention of the particles in the tumor was assessed using high-field (11 T) magnetic resonance imaging (MRI) and by biodistribution of fluorescently labeled conjugates with granzyme B. In vivo therapeutic potential of GrB-SPIONs was tested in different orthotopic glioblastoma models. Therapeutic efficacy of the combined therapeutic approach consisting of GrB-SPIONs and anti-PDL-1 immune checkpoint inhibitors was explored by 3D volumetric MR-imaging. RESULTS: Synthesized GrB-SPION conjugates (ζ-potential -13.2 mV, average size 46 nm) were shown to specifically target Hsp70 membrane-positive tumor cells, in vitro. After internalization of the nanoparticles apoptotic cell death was initiated in a dose-dependent manner (as shown by flow cytometry). Biodistribution studies (employing ultramicroscopy) of fluorescently labeled granzyme B (CdSe quantum dots (QDs)) showed specific accumulation of the protein inside tumor cells. Due to the MR contrast enhancement properties tumor retention of intravenously injected GrB-SPIONs provided tumor imaging of orthotopic gliomas. Monotherapy with GrB-SPIONs in animal models resulted in a significant delay in tumor progression (MRI volumetry) and an increased overall survival. Combining anti-PDL-1 antibodies with GrB-SPIONs elicited a synergistic anticancer activity in mice that was accompanied by an intratumoral infiltration of cytotoxic CD8+ T cells and NK1.1 cells. CONCLUSION: These findings for the first time reveal that a combined therapy consisting of targeting theranostic GrB-SPIONs with immune checkpoint inhibitors synergistically enhances anti-tumor immunity in glioblastoma. The study was supported by Alexander von Humboldt Fellowship, DFG grant SFB824/2, and grant of the Russian Science Foundation 14-50-00068 and by the Federal Agency of Scientific Organizations, Russia, State Grant of the Ministry of Health of the Russian Federation №32.